ANALYSIS OF ISLAMIC LEADERSHIP STYLES AT MUHAMMADIYAH LIMBUNG GOWA HIGH SCHOOL - Sitti Muthmainnah; Muammar Asykur (Academic Bright Collaboration, 2026)
This study aims to analyze the Islamic leadership style applied by the principal at MA Muhammadiyah Limbung. The research seeks to describe the forms of Islamic leadership practiced, identify the factors influencing its implementation, and examine its impact on school effectiveness, teacher performance, organizational climate, and the achievement of educational goals. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews using purposive sampling technique. The informants consisted of the Head of Muhammadiyah Limbung Branch, the Principal, the Head of Administration, and the Chairpersons of Class XI and XII. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing/verification. The findings reveal that the principal of MA Muhammadiyah Limbung demonstrates good decision-making skills in problem-solving. Problems faced by the school can be resolved quickly and thoroughly through a leadership approach that emphasizes Islamic values, thereby supporting the smooth operation of school activities and the achievement of shared goals. The results of this study are expected to provide practical recommendations for improving the quality of Islamic leadership in Muhammadiyah educational institutions. School leaders can use these findings as a reference to strengthen their leadership practices in order to create a more effective, harmonious, and value-based educational environment. This research offers a specific analysis of Islamic leadership styles in the context of a Muhammadiyah senior high school (MA), focusing on real practices at MA Muhammadiyah Limbung. It contributes to the limited body of literature on Islamic leadership implementation in secondary Islamic education institutions in South Sulawesi.